Alternative Assessment Strategies and Challenges in Mathematics Instruction at MSU-Sulu during the COVID-19 Pandemic - Sharifa M. Jalaidi (Future Science / FSH-PH Publications, 2026)
A shift in learning modalities has been brought about by the pandemic. This is true in regard to all subject areas. Even higher educational institution is faced with unprecedented challenges due to this. However, as many papers focused on alternative learning modalities, few centered on the alternative assessment strategies, which would give a necessary perspective on how the students are being assessed and how they view these assessment strategies. Hence, the researcher opted to conduct this study entitled Alternative Assessment Strategies and Challenges in Mathematics Instruction in the time of the COVID-19 Pandemic. The study mainly centers on Mathematics due to the nature of the subject that usually makes use of drills in measuring the capability of students to solve problems relating to different fields of the subject, as well as considering that it is perceived to be one of the difficult subjects even in higher education. The study identified the alternative assessment strategies used in Mathematics instruction during the pandemic as well as the challenges associated with them. It was also assessed whether there were factors affecting the use of the strategies. The study also looked for the association between the perceived efficiency of the alternative assessment strategies and the challenges faced by the students. With the use of a cross-sectional survey design, two survey questionnaires, and various statistical tools to analyze the data, such as arithmetic mean, weighted mean, t-test, one-way analysis of variance, and correlation analysis, the problems of the study were answered.